Year-round records of bulk and size-segregated aerosol composition in central Antarctica (Concordia site) - Part 1: Fractionation of sea-salt particles - Legrand, Michel; Preunkert, Susanne; Wolff, Eric; Weller, Rolf; Jourdain, Bruno; Wagenbach, Dietmar (Atmospheric chemistry and physics, 2017)
Abstract. Multiple year-round records of bulk and size-segregated composition of aerosol were obtained at the inland site of Concordia located at Dome C in East Antarctica. In parallel, sampling of acidic gases on denuder tubes was carried out to quantify the concentrations of HCl and HNO3 present in the gas phase. These time series are used to examine aerosol present over central Antarctica in terms of chloride depletion relative to sodium with respect to freshly emitted sea-salt aerosol as well as depletion of sulfate relative to sodium with respect to the composition of seawater. A depletion of chloride relative to sodium is observed over most of the year, reaching a maximum of ∼ 20 ng m−3 in spring when there are still large sea-salt amounts and acidic components start to recover. The role of acidic sulfur aerosol and nitric acid in replacing chloride from sea-salt particles is here discussed. HCl is found to be around twice more abundant than the amount of chloride lost by sea-salt aerosol, suggesting that either HCl is more efficiently transported to Concordia than sea-salt aerosol or re-emission from the snow pack over the Antarctic plateau represents an additional significant HCl source. The size-segregated composition of aerosol collected in winter (from 2006 to 2011) indicates a mean sulfate to sodium ratio of sea-salt aerosol present over central Antarctica of 0.16 ± 0.05, suggesting that, on average, the sea-ice and open-ocean emissions equally contribute to sea-salt aerosol load of the inland Antarctic atmosphere. The temporal variability of the sulfate depletion relative to sodium was examined at the light of air mass backward trajectories, showing an overall decreasing trend of the ratio (i.e., a stronger sulfate depletion relative to sodium) when air masses arriving at Dome C had traveled a longer time over sea ice than over open ocean. The findings are shown to be useful to discuss sea-salt ice records extracted at deep drilling sites located inland Antarctica.